PERLINDUNGAN HUKUM TERHADAP KONSUMEN TERKAIT KASUS JUAL BELI MOTOR ONLINE - Widiadnyani, I Gusti Ayu; Swetasoma, Cokorda Gede (Jurnal Yustitia, 2025)
The development of digital technology has encouraged an increase in online motorbike buying and selling transactions. However, in practice, many consumers face risks such as inaccurate information, fraud, or a discrepancy between the condition of the vehicle and what was promised. Legal protection for consumers in these transactions is very important to guarantee their rights and prevent harmful business practices. This research aims to analyze legal protection for consumers in cases of online motorbike buying and selling based on Law Number 8 of 1999 concerning Consumer Protection and related regulations such as the Civil Code and the Information and Electronic Transactions Law. Business actors have an obligation to provide correct and not misleading information, while consumers have the right to protection if violations occur. If a dispute occurs, consumers can take legal action through the Consumer Dispute Resolution Agency, such as civil lawsuits, reporting to the police if there are criminal elements such as fraud. Even though there are regulations governing consumer protection, the effectiveness of their implementation still needs to be strengthened through stricter supervision and education for consumers to be more alert when making online transactions.